A single DNA response element can confer inducibility by both alpha- and gamma-interferons. - Reid, L E (1989)
Genomic and cDNA clones corresponding to 9-27, a member of the human 1-8 gene family highly inducible by alpha- and gamma-interferons (IFNs), have been isolated and characterized. A 1.7-kilobase genomic clone contains a complete functional gene with two exons, encoding a 125-amino acid polypeptide of unknown function. The 5' flanking region of the gene contains a 13-base-pair IFN-stimulable response element (ISRE), homologous to the ISREs of the 6-16, ISG 15, and ISG 54 genes, which are predominantly inducible by IFN-alpha, beta. Analysis of constructs containing native and mutated ISREs suggests that this motif is essential for the response of 9-27 to IFN-gamma as well as IFN-alpha. Furthermore, the 9-27 (GGAAATAGAAACT) and 6-16 (GGGAAAATGAAACT) ISREs can each confer a response to both types of IFN when placed on the 5' side of a marker gene. Since the 6-16 gene does not normally respond to IFN-gamma, the context of the ISRE must determine the specificity of the response.